Summer at mustang ridge eaudiobook - Hayworth, Jesse (Mustang Ridge, 2015)
Recovering from a difficult divorce and having problems with her daughter, Shelby accepts a summer job cooking at a family-run dude ranch. She hopes the animals will be just what her daughter, Lizzie, needs. Little does she know that ranch life will work some healing magic on her too. When Shelby meets the head wrangler, Foster, she is put off by his brusque nature, but Lizzie takes an instant liking to the cowboy and his horses. While both Foster and Shelby have been scarred by love, it's not long before Shelby is drawn to the rugged cowboy and his thoughtful ways. But with summer nights in short supply and Foster wary of falling for a city girl, a simple summer romance soon grows complicated. As the days dwindle, Shelby will have to decide not only what is best for her daughter, but also where her future—and her happiness—will be found.